Adoption of Fisheries Diversification Innovation in Poklahsar in Cigasong Sub-District, Majalengka District - Yuniarti, Tatty; Adinda Putri, Jasmine; Junita Puspa Dewi, Ita; Leilani, Ani (Jurnal Penyuluhan, 2020)
Cigasong District has fisheries potential like poklahsars. Poklahsar produces rebon shrimp brittle and carp. The development of fisheries potential can be done by diversifying processed fish. The research aims to study (1)changes in knowledge, attitudes, and skills of poklahsar after counseling on diversification of processed fisheries; (2) the process of adopting innovations; (3) the group that adopts the best innovation. Counseling was carried out using a demonstration method of diversification of processed fish. Respondents are members of poklahsar Sehati, Mitra Harapan and Pandawa Opat. Responses were observed using questionnaires, interviews, and observations; the data is displayed descriptively and simple tabulations are diagrams. The results showed; (1) an increase in knowledge, attitudes and skills in the whole poklahsar; (2) the process of adopting innovations in each group is different; (3) the results of the evaluation of the adoption of krispi eel innovation in poklahsar Sehati have the highest value of attitude change that is 10 and the value of knowledge 4, faster to implement than other poklahsar that is on the 5th week by two respondents from seven respondents, the 6th week the number of adopters increased into seven people and included in the early adopter category.